ASSOCIATION OF THYROID FUNCTION TEST WITH POST-COVID-19 PCR-NEGATIVE PATIENTS - Abid Ali Khawaj,; Sabahat Asghar,; Samman Khurshid,; Noreen Taj,; Rubina Faisal Paul,; Fozia Jehangir, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Corona virus diseases-19 (COVID-19) infection has shown many complications in all organ systems, like thyroid gland, during the acute phase and in the post-COVID-19 period. The aim of this study was to find the risk of hypo-functioning thyroid gland during post COVID-19 period as a chronic complication for possible follow up and management implications. Methods: This combined retrospective-prospective study was conducted over a period of nine months at tertiary care hospitals, Ayub Medical Complex Abbottabad and King Abdullah Hospital, Mansehra. Through non-probability convenient sampling technique, data was collected from 160 records at the hospitals. Confirmed cases of COVID-19, after their consent, were measured for thyroid hormones at two, four and eight weeks. Data was analyzed using Chi-square test. p-value less than 0.05 was considered as significant. Results: Out of 160 study participants, majority 102 (63.75%) were males and 58 (36.25%) were females with mean age of study population of 47.41±14.29 years. The frequency of hypothyroidism decreased over eight weeks from 8 (38.09%) to 6 (28.57%). While subclinical hypothyroidism decreased from 14 (36.89%) to 12 (30.76%). There was a very highly significant (p= 0.0001) association between proportions of hypothyroidism, Euthyroid Sick Syndrome and Subclinical hypothyroidism, and proportions of euthyroid patients in post COVID-19 period over eight weeks. Conclusion: Subclinical hypothyroidism, overt hypothyroidism, Euthyroid Sick Syndrome, and thyrotoxicosis are manifestations of hypo functioning thyroid gland. There is a need to monitor patients over a period of as short as two weeks to two months and beyond for possible detection of these complications of COVID-19 for appropriate management.